Millennial travel vlogs: emergence of a new form of virtual tourism in the post-pandemic era?. (27th July 2021) - Chakravarty, Urjani; Chand, Gulab; Singh, Udaya Narayana
Abstract : Purpose: This paper aims to present the authors' perspectives on the new narrative styles adopted by international millennial travel vloggers during the COVID-19 pandemic. They aim to promote virtual tourism, and the authors present six examples of millennial vloggers. Considering tighter government regulations relating to travel, vloggers have developed novel ways of content creation through "travel writing." Design/methodology/approach: The authors used narrative analysis to review their sample of vlogs and how specific changes in each vlogging stage are motivated by viewer expectancy. Findings: Millennial vlogger couples are using the YouTube platform to meet the demand for virtual tourism. Research limitations/implications: This study provides new ways of looking at travel vlogging as an occupation and means of entertainment. However, the current dynamic situation may well lead to further challenges for this kind of research. Practical implications: The implications relate to the provision of a better understanding of the scope for virtual tourism and how it can lead to new avenues for tourism development. Originality/value: The authors reviewed millennial vloggers during the COVID-19 pandemic and applied narratology to the vlogs to better analyse the changes caused by the pandemic.